Are tumour grade and tumour budding equivalent in colorectal cancer? A retrospective analysis of 771 patients. (May 2020) - Zlobec, Inti; Dawson, Heather E.; Blank, Annika; Bokhorst, John-Melle; Berger, Martin D.; Nagtegaal, Iris D.; Lugli, Alessandro
Abstract: Background: Tumour grade is traditionally considered in the management of patients with colorectal cancer. However, a large body of literature suggests that a related feature, namely tumour budding, may have a more important clinical impact. The aim of our study is to determine the correlation between tumour grade and tumour budding and their impact on patient outcome. Methods: A retrospective collective of 771 patients with colorectal cancer were included in the study. Clinicopathological information included tumour grade (World Health Organisation 2010; G1, G2 and G3) and tumour budding evaluated as BD1, BD2 and BD3 and representing 0–4 buds, 5–9 buds and 10 or more buds per 0.785 mm 2, respectively. Results: Tumour grade and tumour budding were correlated (p < 0.0001, percent concordance: 33.8%). Of the BD1 cases, 18.1% were of G3. Only two BD3 cases were G1. Both high tumour grade and tumour budding were associated with higher pT, lymph node metastasis, distant metastasis and lymphatic and venous vessel invasion (p < 0.01, all), but only tumour grade was additionally associated with right-sided tumour location and mucinous histology. Higher tumour budding led to worse overall (p = 0.0286) and disease-free survival (p = 0.001), but tumour grade did not. Budding was independent of tumour grade in multivariate analysis. Discussion: Tumour grade and tumour budding are distinct features, as recognised by their different clinicopathological associations, reflecting different underlying biological processes. Nonetheless, tumour budding seems to outperform tumour grade in terms of predicting disease-free survival. Highlights: Tumour budding is not equivalent to tumour grade in colorectal cancer. Both tumour grade and tumour budding are associated with aggressive tumour features. Tumour budding outperforms tumour grade as a prognostic factor. Both contribute different information and should be reported in colorectal cancer.